Study of application of bioclimatic architecture strategy at Citraland Residential House in Palu City - Salenda, Hariyadi; Winarta, A; Khaerunnisa, Khaerunnisa; Abidin, A (ASCEE, 2024)
Palu City has a fairly hot air temperature, very high intensity of solar radiation, quite high rainfall, and a fairly large wind speed. When reviewing the climatic conditions of Palu City above, the planners in this case the Citraland housing architect team should be able to apply a bioclimatic architecture strategy to be able to respond to the climatic conditions of the city of Palu. Based on this background, it is necessary to conduct a research study on the application of bioclimatic architecture strategies in Citraland's residences. This study uses a rationalistic approach with an exploratory method. Research shows that Citraland Residence has implemented a bioclimatic architectural strategy in several ways, namely the use of shading or shadow effects in the form of roof canopy, eaves, and lattice made of wood, and protective plants, as well as the use of insulating materials such as natural stone affixed to the outer walls. residential home. In addition, the layout of the residence also plays a role in the flow of air circulation to the maximum. Then the strategy of making wind-catching rooms and the use of glass materials on several sides of the building which acts as a place to enter sunlight into the house